Effect of training-session intensity distribution on session rating of perceived exertion in soccer players - Fanchini, M.; Ghielmetti, R.; Coutts, A. J.; Schena, F.; Impellizzeri, F. M. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To examine the effect of different exercise-intensity distributions within a training session on the session rating of perceived exertion (RPE) and to examine the timing of measure on the rating. Methods: Nineteen junior players (age 16 ± 1 y, height 173 ± 5 cm, body mass 64 ± 6 kg) from a Swiss soccer team were involved in the study. Percentage of heart rate maximum (%HR) and RPE (Borg CR100®) were collected in 4 standardized training sessions (conditions). The Total Quality of Recovery scale (TQR) and a visual analogue scale (VAS) for pain of the lower limbs were used to control for the effect of pretraining fatigue. Every session consisted of three 20-min blocks of different intensities (ie, low-moderate-high) performed in a random order. RPE was collected after every block (RPE5), immediately after the session (RPE-end), and 30 min after the session (RPE30). Results: RPE5s of each block were different depending on the distribution sequence (P < .0001). RPE-end, TQR, and VAS values were not different between conditions (P = .57, P = .55, and P = .96, respectively). The %HR was significantly different between conditions (P = .008), with condition 3 higher than condition 2 (74.1 vs 70.2%, P = .02). Edwards training loads were not significantly different between conditions (P = .09). RPE30 was not different from RPE-end (P > .05). Conclusions: The current results show that coaches can design training sessions without concern about the influence of the within-session distribution of exercise intensity on session-RPE and that RPE can be collected at the end of the session or 30 min later.